The effectiveness of person-centred planning for people with intellectual disabilities: A systematic review. (October 2016) - Ratti, V.; Hassiotis, A.; Crabtree, J.; Deb, S.; Gallagher, P.; Unwin, G.
Highlights: There were 7 quantitative, 5 qualitative and 4 mixed methods studies. PCP was most effective for community participation. The methodological quality of the included studies was moderate to weak. The evidence for wide implementation of PCP remains inconclusive. Abstract: Objectives: To evaluate the effectiveness of Person-Centred Planning (PCP) on outcomes for individuals with intellectual disabilities (ID) across the age range. Method: The electronic databases PsycInfo, Embase, CINHAL, PubMed, Web of Science, Scopus and Medline were searched for studies evaluating the impact of PCP on people with ID, published between 1990 and 2014; these were supplemented by manual searches of reference lists. Studies were considered irrespective of methodology, sample size and publication source, if outcomes reflected the impact of PCP on individuals with ID. Results: Seven quantitative, five qualitative and four mixed methods studies were included in the review. The overall quality of the evidence was low but suggestive that PCP may have a positive, yet moderate, impact on some outcomes for individuals with ID, particularly community-participation, participation in activities and daily choice-making. For other outcomes such as employment the findings were inconsistent. Conclusion: The evidence supporting the effectiveness of PCP is limited and does not demonstrate that PCP can achieve radical transformations in the lives of people with ID. Clearer descriptions of PCP and its components are needed. Small-scale successful demonstrations of effectiveness exist, but its clinical, cost-effectiveness and wider implementation must be investigated in large scale studies.